Penyelesaian Sengketa Hak Milik Terkait Penguasaan Tanah Bangunan Studi Kasus Putusan Pengadilan Semarang - Dina Jessica; Ana Silviana (Universitas Batanghari Jambi, 2023)
The object of this article is decision No. 414/Pdt/2020/PT SMG which decides the dispute over land ownership rights caused by still being controlled and owned by other parties. This study aims to determine the judge's considerations in deciding and stating the decision on disputes over rights to building land objects that have been purchased but cannot be controlled and owned, as well as legal consequences after the decision on disputes over rights to building land objects that have been purchased but cannot be controlled and owned. determined by the judge. This research method uses a normative juridical approach because it examines legal aspects and legal rules with library materials, namely books, accredited journals, laws and regulations, Civil Codes, and Theses. The research specification uses descriptive analysis law, with a case approach. The results showed that there was a problem in the process of buying and selling land by the Defendant/Appellant and the Comparator, even though the buying and selling process was by the Deed of Sale and Purchase number 607/Kaliwungu/2006. The control of land by the Defendant/Appellate in the case of the dispute over land ownership rights, decision number 414/Pdt/2020/PT SMG is invalid and null and void. Besides that, the legal consequence is that the Defendant/Appellate vacate and submit the object of a dispute to the Plaintiff and if necessary with State Security Equipment.